Android Based Multimedia Learning for Vocational High Schools - Nurhikmah Hasyim; Hamsu Abdul Gani; Sukarno Hatta (Universitas Negeri Makassar, 2020)
This This research is developing multimedia based on Andorid for vocational high school students in Makassar city. The development model used is an interactive multimedia design development model developed by StephenaM. Alessi & Stanley R. Trollip consists of planning, design and development, as well as attributes that are always present in every stage. The data collection techniques used questionnaires, interviews and documentation which were analyzed descriptive qualitative and quantitative statistics. The results showed 1) the use of the internet in learning has not been maximal, including the use of smartphones, while the development of information and communication technology demands the use of information teccnology in learning, 2) Android-based multimedia that has been developed has been validated by content expert and media expert and declared valid and very proper to be used, 3) the trial results in the individual test are in a score with very proper qualifications so that they are declared valid meanwhile the small group trials are in the very valid and practical. Based on the stages that are passed in Android-based multimedia development in physic subject, product development can be continued at the next stage, namely large group testing and implementation.